KESEDIAAN CALON BIDAN UNTUK BEKERJA DI DAERAH TERPENCIL - Nurhira Abdul Kadir (Universitas Islam Negeri Alauddin Makassar, 2017)
Various factors affect the willingness of future midwives to work in remote areas. Individual characters, self-motivation, education and incentives are among things considered to determine that willingness. This descriptive study compares final-stage students from urban and rural midwiferyeducational institutions in terms of their willingness to accept rural posting, the reasons for the willingness, the expectation towards and the duration of the assignment. Questionnaires were distributed to the two groups, 116 students from rural institution and 85 students from urban institution. The study found that the majority of respondents from both groups were 21 years of age or older and had a GPA of 3 or more. The respondents from both institutions mostly said they were willing to work in remote areas. The most dominant reasons for that were to serve the benefit of society and to add experience. Most students from both institutions expect the fulfillment of facilities and infrastructure to work. Duration of 1 and 2 years of assignment attracts respondents in both institutions but most rural students choose a period of 3 years. This research is expected to contribute to improving the regulation of midwife remote placement and also that future research can explore much deeper aspects such as respondents’ characteristics and their relation to the' willingness for doing rural posting.